Akulturasi: Strategi Walisongo dalam menyatukan Islam dengan Budaya - Mawati, Tiarah (Maliki Interdisciplinary Journal, 2024)
This article discusses accuturation as a strategy used by Walisongo in preaching by integrating Islamic elements into the culture of the local community. The discussion began with an understanding of acculturation theory, then an in-depth discussion of Walisongo’s acculturation strategy and the impact arising from the implementation of this strategy. In this article, the author uses qualitative research methods to gain an in-depth understanding. The results of the acculturation strategy carried out by Walisongo itself have proven to be effective in launching the mission of spreading Islam, because this strategy makes it easier for the guardians to preach by integrating into the culture of the community, so that they will feel safe without worrying that the arrival of immigrants will threaten their culture.